Navigation-grade interferometric air-core antiresonant fibre optic gyroscope with enhanced thermal stability - Maochun Li; Yizhi Sun; Shoufei Gao; Xiaoming Zhao; Fei Hui; Wei Luo; Qingbo Hu; Hao Chen; Helin Wu; Yingying Wang; Miao Yan; Wei Ding (Nature Communications)
Abstract We present a groundbreaking navigation-grade interferometric air-core fibre optic gyroscope (IFOG) using a quadrupolar-wound coil of four-tube truncated double nested antiresonant nodeless fibre (tDNANF). This state-of-the-art tDNANF simultaneously achieves low loss, low bend loss, single-spatial-mode operation, and exceptional linear polarization purity over a broad wavelength range. Our 469 m tDNANF coil demonstrated a polarization extinction ratio (PER) of ~20 dB when illuminated by an amplified spontaneous emission (ASE) source spanning 1525-1565 nm. Under these conditions, the gyro archives an angular random walk (ARW) of 0.00383 deg h−1/2 and a bias instability (BI) drift of 0.0017 deg h−1, marking the first instance of navigation-grade performance in air-core FOGs. Additionally, we validated the low thermal sensitivity of air-core FOGs, with reductions of 9.24/10.68/6.82 compared to that of conventional polarization-maintaining solid-core FOGs of the same size across various temperature ranges. These results represent a significant step towards long-standing promise of high-precision inertial navigation applications with superior environmental adaptability.